Analisis Lose dan Gain Produksi Overburden Berdasarkan Implementasi Plan Production Schedule - Nababan, Berkat Obniel; Virgiyanti, Lisa; Inso, Yos David; Iashania, Yunida; Murati, Ferra (Universitas Pahlawan Tuanku Tambusai, 2025)
PT Fontana Resources Indonesia is a company engaged in the coal mining business. The target amount of overburden production based on the schedule in May 2024 is 218,580.61 BCM. The production results with actual calculation are 105,469.55 BCM, while based on calculations from excavator activities the actual overburden production is 191,491.62 BCM. The difference in calculations based on production targets with mine progress is the background for conducting this research. The methods used in this research are descriptive methods and quantitative methods. The actual volume of overburden is obtained from the calculation of production by the loader (excavator), where the volume of actual overburden production calculation will be compared with the production target set in the plan production schedule. The target volume of overburden production compared to the actual overburden production volume has a deviation of 27,088.99 BCM with an achievement of 88%.